Ответы и объяснения

2014-04-08T18:18:26+00:00
6*x+8=14+30    
6х= 44-8
6х = 36
х = 36/6 
х = 6

20 +4*x=52   
4х = 52 - 20
4х = 32
х = 32/4
х = 8

5*(x+4)-43=17
5х + 20 - 43 = 17
5х = 17-20+43
5х = 40
х = 40/5
х = 8

2014-04-08T20:11:01+00:00
6*х+8=44        4*х=52-20           5*(х+4)=17+43
6*х=44-8          4*х=32               5*(х+4)=60
6*х=36            х=32:4                 х+4=60:5
х=36:6            х=8                     х+4=12
х=6                                            х=12-4
                                                 х=8